Application of Educational Supervision in Improving Teacher’s Professionalism - Anggrayni, Retno (PPSDP International Journal of Education, 2024)
This qualitative study aims at analyzing educational supervision in improving teacher’s professionalism. Supervision is an activity carried out by the principal to supervise and direct all educational devices in order to achieve educational goals. The principal is responsible for implementing the supervision program, which starts from planning, implementation, and follow-up, and includes overseeing and directing the entire educational system to achieve academic goals. The results of the research showed that 1) the application of educational supervision in improving teacher’s professionalism were the principal is active in checking the lesson plan every month; the principal is active in conducting class visits; the principal is active in supervising education at the beginning of each month by evaluating teachers; the principal always participates in PKKS activities which are held every year; and 85% of teachers in linear institutions; 2) the implementation of educational supervision can be said effective in improving teacher’s professionalism because teacher’s professionalism becomes better starting from planning, implementing to learning evaluation.